2019
DOI: 10.1159/000496739
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Medical Needs in Ulcerative Colitis: An Expert Group Consensus

Abstract: Background: The authors aimed to conduct an extensive literature review and consensus meeting to identify unmet needs in ulcerative colitis (UC) and ways to overcome them. UC is a relapsing and remitting inflammatory bowel disease with varied, and changing, incidence rates worldwide. UC has an unpredictable disease course and is associated with a high health economic burden. During 2016 and 2017, a panel of experts was convened to identify, discuss and address areas of unmet need in UC. Methods: PubMed and Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 88 publications
0
57
0
1
Order By: Relevance
“…In addition, there is an urgent need for alternative therapies for IBD patients, which do not respond to current first-line treatments. 45 To help meet this clinical gap, we propose the possibility of screening specifically for patients for NE activity and treating this subset with NE inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is an urgent need for alternative therapies for IBD patients, which do not respond to current first-line treatments. 45 To help meet this clinical gap, we propose the possibility of screening specifically for patients for NE activity and treating this subset with NE inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…European guidelines recommend sustained steroid-free remission as the treatment goal. [7][8][9] Despite these options, some patients with UC require a colectomy. 10 The highest colectomy rates are seen during the first few years after diagnosis.…”
Section: Key Messagesmentioning
confidence: 99%
“…Despite these limitations, this analysis confirmed a continuing unmet need in UC, although a number of biologic treatment options are available. Treatment options other than new biologics might have advantages: the secondary loss of response to biologics is a potential issue, as a discrete-choice study has shown that in UC long-term symptom control is the attribute most valued by both physicians and patients 45 ; biologics require parenteral administration, and there is evidence that oral administration is preferred by patients with UC 7,46 ; and numerous studies have shown biologics to have poor cost-effectiveness , [47][48][49] .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for UC include aminosalicylates (5-ASA), corticosteroids, immunosuppressants, biologics (tumor necrosis factor inhibitors and anti-integrins), calcineurin inhibitors, the JAK inhibitor tofacitinib, and surgery as an option for non-responsive patients 7 . Guidelines recommend that treatments are selected based on disease site, severity and current activity [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%